2019
DOI: 10.1590/1806-9061-2018-0941
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Breast Meat Collected from Spent Lohmann Brown Layers in Comparison to Commercial Ross Broilers

Abstract: The objective of this study was to compare characteristics and properties of breast meat from spent Lohmann Brown layers (SP, 90 weeks old, n = 24) and those of commercial broilers (BR, 6 weeks old, n = 24). The breasts of both SP and BR were collected from a local processing plant, vacuum-packed in a plastic bag, and stored at-18ºC until further analyses. The SP showed a greater water-holding capacity, tougher and chewier texture (p<0.05). Both raw and cooked SP breasts comprised the greater total collagen bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 53 publications
(63 reference statements)
3
6
0
Order By: Relevance
“…The same happens with the values obtained for the TPA test. Our results were satisfactory compared with those reported in the literature for laying hens, since they were lower than those previously reported (Chueachuaychoo et al, 2011;Khwunsiri et al, 2007;Limpisophon et al, 2019).…”
Section: Breed Effect On Textural Parameters Of Breastsupporting
confidence: 68%
See 4 more Smart Citations
“…The same happens with the values obtained for the TPA test. Our results were satisfactory compared with those reported in the literature for laying hens, since they were lower than those previously reported (Chueachuaychoo et al, 2011;Khwunsiri et al, 2007;Limpisophon et al, 2019).…”
Section: Breed Effect On Textural Parameters Of Breastsupporting
confidence: 68%
“…In the present study, CF group samples showed higher textural parameters for hardness which could be attributed to the lower cooking loss percentage (higher water holding capacity) of the meat assessed. However, the tough texture assessed for the CF group (diet effect) could also be attributed to other parameters not assessed in the present study (e. g. muscle fibre size and arrangement; connective tissue amount, spatial distribution, and composition; and post-mortem biochemical events) (Limpisophon et al, 2019). Hence, further investigations should be realized to evaluate the diet effect on the abovementioned parameters to corroborate our results.…”
Section: Diet Effect On Textural Parameters Of Breastsupporting
confidence: 59%
See 3 more Smart Citations